DETERMINANTS OF ORGANIZATIONAL COMMITMENT AND ITS IMPLICATION ON TURNOVER INTENTION AT THE FOODHALL IN DKI JAKARTA PROVINCE - Nazifah Husainah; Harries Madiistriyatno (Dinasti International Journal of Education Management And Social Science, 2020)
The purpose of this study was to determine the effect of organizational culture, career development, compensation and organizational commitment partially or simultaneously on employee turnover intention. The population in this study amounted to 1,982 employees at twenty-five outlets of The Foodhall in DKI Jakarta Province, with a total sample of 355 respondents. The research method used in this research is descriptive and explanatory survey methods. The sampling method is probability sampling with proportional random sampling technique, and the data analysis method used is SEM (Structural Equation Modeling) with data analysis tools Lisrel 8.80. Based on the research results obtained the following findings: organizational culture, career development, and compensation partially and simultaneously have a significant effect on organizational commitment with a contribution of 58%. Partially career development which is reflected in career doubt has a positive and dominant effect on organizational commitment. Organizational culture, career development, compensation and organizational commitment either partially or simultaneously have a significant effect on employee turnover intention with a contribution of 81%. Partially, organizational commitment has the most dominant influence on employee turnover intentions. The results also show that organizational commitment is a fully mediating variable on the influence of organizational culture, career development, and compensation on employee turnover intention. The managerial implication of this research is that the turnover intention of The Foodhall's employees in Jakarta, which is reflected in the dimension of stopping work, will decrease if The Foodhall in Jakarta is able to increase organizational commitment which is reflected in sustainable commitment, while organizational commitment will increase if The Foodhalls in Jakarta can improve career development. employees who are reflected in career doubts which are supported by an increase in organizational culture which is reflected in the dimensions of results orientation and also supported by an increase in compensation given to employees which is reflected in the high level of indirect compensation.